Using phenotyping to visualize and identify selfish bacteria: a methods guide - G. Reintjes; G. Giljan; B. M. Fuchs; C. Arnosti; R. Amann (Microbiology Spectrum)
ABSTRACT Polysaccharides are dominant components of plant and algal biomass, whose degradation is typically mediated by heterotrophic bacteria. These bacteria use extracellular enzymes to hydrolyze polysaccharides to oligosaccharides that are then also available to other bacteria. Recently, a new mechanism of polysaccharide processing—“selfish” uptake—has been recognized, initially among gut-derived bacteria. In “selfish” uptake, polysaccharides are bound at the outer membrane, partially hydrolyzed, and transported into the periplasmic space without loss of hydrolysis products, thus limiting the availability of smaller sugars to the surrounding environment. Selfish uptake is widespread in environments ranging from the ocean’s cool, oxygen-rich, organic carbon-poor waters to the warm, carbon-rich, anoxic environment of the human gut. In this methods paper, we present a detailed guide to identifying selfish bacteria, including techniques for rapidly visualizing selfish uptake in complex bacterial communities, detecting selfish organisms, and distinguishing their activity from that of other community members.IMPORTANCEUnderstanding the role of heterotrophic bacteria in the degradation of organic matter is critical for comprehending carbon cycling and microbial ecology across different environments. This study highlights the significant prevalence of “selfish uptake” among bacteria—often overlooked by standard microbial activity assessments—and presents the method used to quantify and identify these “selfish” bacteria. Found in diverse habitats such as anoxic gut environments, oxygenated waters, sediments, and soils, their widespread presence underscores the necessity of revisiting current methodologies to include these crucial organisms. By identifying and studying selfish bacteria, we can gain detailed insights into how microbial communities function, how carbon flows through ecosystems, and how these processes impact global biogeochemical cycles.